Desain Silabus Bahasa Arab Responsif Kebutuhan: Analisis Tipologi dan Prinsip Penyusunan di Lingkungan Perguruan Tinggi Keagamaan Islam - Ahid Ilham Zulfiqar; Acep Hermawan; Eva Latifah Fauzia (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
Syllabus design occupies a paradoxically central yet underexplored position in Arabic language education at Indonesian Islamic Higher Education institutions (PTKIN). Through a descriptive-analytical library research methodology, this article examines three foundational dimensions of Arabic syllabus construction: conceptual definitions, typological classification, and design principles. Analysis of international and Indonesian scholarship reveals that five major syllabus typologies (structural, notional-functional, situational, task-based, and integrative) carry distinct pedagogical implications that must be carefully matched to institutional contexts and learner profiles. Six interconnected design principles are theorized: relevance, gradation, integration, flexibility, goal-orientation, and authenticity. The study argues that integrative syllabus frameworks, which deliberately combine structural, functional, and task-based elements, best accommodate the linguistic complexity of Arabic and the heterogeneous learning goals characteristic of PTKIN students. Practical implications for curriculum designers, classroom instructors, and institutional policymakers are elaborated, and empirical implementation studies are proposed as an urgent scholarly priority for Arabic language education in Indonesia.